THE INFLUENCE OF SALES PROMOTION AND HEDONIC SHOPPING MOTIVATION ON IMPULSIVE BUYING AT SPECIAL EVENT DAY of ONLINE MARKETPLACE - Almas Naavi; Mahir Pradana (JURNAL EDUCATION AND DEVELOPMENT, 2024)
This research was conducted to determine the effect of sales promotions and hedonic shopping motivation on impulse purchases at Shopee's special event day marketplace (case study in generation Z). The method used in this research is a non-probability sampling method and uses a purposive sampling technique, and the data is processed using the SPSS version 29 application. The results of this research show that Sales promotions on Special Event Days and Hedonic Shopping Motivation influence Impulsive Buying on Shopee Marketplace, Sales Promotion on Special Event Day has no effect on Impulsive Buying on Shopee Marketplace, Hedonic Shopping Motivation has an effect on Impulsive Buying on Shopee Marketplace.